Einstein-Cartan gravity model with f-essence - Мадиярова, А; Разина, О; Цыба, П (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
This article discusses the Einstein-Cartan gravity model with f-essence in four dimensions together with the homogeneous, isotropic and flat Friedmann-Robertson-Walker Universe. A system of equations of motion has been found for this model. A power solution is constructed for the scale factor a = a0t α . For an accelerated expansion of the Universe, α > 1 is necessary. The fermion potential has been restored. For a more complete description of the kinematics of cosmological expansion, the energy density, pressure, parameter of the equation of state, deceleration parameter, jerk parameter and snap parameter were found. Energy conditions studied. These conditions impose model-independent constraints on the behavior of energy density and pressure. Appropriate graphics are made.